IgG Subclasses in Selective IgA Deficiency: Importance of IgG2-IgA Deficiency - Oxelius, Vivi-Anne; Laurell, Anna-Brita; Lindquist, Bertil; Golebiowska, Henryka; Axelsson, Uno; Björkander, Janne; Hanson, Lars Å (The New England journal of medicine, 1981)
A SELECTIVE deficiency in IgA appears in about one in 700 persons. 1 Many of these persons are healthy, 2 but there is an increased frequency of infections, autoimmune disorders, atopy, and malabsorption syndromes in such subjects. 3 In an attempt to explain why some IgA-deficient patients have illnesses and others do not, we measured IgG subclasses in patients with selective IgA deficiency with and without disease. We found coexisting IgG2 deficiency in some of the diseased patients but not in the healthy subjects. Methods We obtained serum samples from 37 patients (22 children one to 14 years old and 15 adults) with . . .